Health Impact of Domestic Violence against Saudi Women: Cross Sectional Study - Al-Dosary, Ahmad Hamad (International Journal of Health Sciences, 2016)
Abstract Objective: Domestic violence is a major public health problem.Â A wide range of health hazards result from violence against women directly, or from its long-term consequences. The objective of this study is to determine health related consequences of domestic violence against women. Method: A community based cross-sectional study was carried through online survey; convenience sample was taken during the period between December 2013 and February 2014. 421 women completed the survey, who met the inclusion criteria and accepted willing to be a part of this study. The data was collected through online survey website. A validated Arabic version of NorVold Domestic Abuse Questionnaire (NOVAQ) was used as a tool to assess domestic violence among the study sample. Analysis was performed using SPSS, version 18.0. Results: A total of 421 women participated in the survey. There was no significant correlation between socio-demographic characteristics and being abused or not. However, by further analysis we found more sexual abuse among non-working women P=0.048. There was significant correlation between abused women and general health status, doctor visits, depression, insomnia, and somatic symptoms. Conclusion: The consequences of abuse are profound, extending beyond the health of individual to affect the well-being of entire community. So, we recommend to increase community awareness through national awareness campaign, national prevalence survey of domestic violence and well trained health professionals for assessing domestic violence cases. Â